REKOMENDASI PEMILIHAN PELATIHAN TENAGA KERJA PADA INDUSTRI KREATIF KERIPIK MENGGUNAKAN AHP COPRAS - Khusna, Khanifatul; Muhsyi, Abdul; Fauziyyah, Salma; Rahmatillah, Maria Ulfa Nur (Jurnal Ilmiah Ekonomi Bisnis, 2024)
Human Resources is an asset for a company that has an important role, thus proper training is very important in managing the workforce. High competence in an organization certainly determines how good the quality of human resources it has and determines the competitive ability of a company. The purpose of this research is to analyze the selection of appropriate training for human resources at Agung Food where these MSMEs have processed tuna products. Agung Food's address is in Sukorambi District, Jember Regency. The approach in this study is a quantitative approach by collecting data using questionnaires. The analytical tools used are the AHP and COPRAS methods. The results obtained through this ranking system put creativity training in the first rank, while the second rank is cross-functional training and the last rank is skill training.